1998
DOI: 10.1104/pp.117.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of O-Methyltransferase Gene by Homologous Sense Transgene in Quaking Aspen Causes Red-Brown Wood Phenotypes1

Abstract: Homologous sense suppression of a gene encoding lignin pathway caffeic acid O-methyltransferase (CAOMT) in the xylem of quaking aspen (Populus tremuloides Michx.) resulted in transgenic plants exhibiting novel phenotypes with either mottled or complete red-brown coloration in their woody stems. These phenotypes appeared in all independent transgenic lines regenerated with a sense CAOMT construct but were absent from all plants produced with antisense CAOMT. The CAOMT sense transgene expression was undetectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
84
4
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 53 publications
7
84
4
2
Order By: Relevance
“…Because COMT was considered to be the sole enzyme involved in methylation, COMT had long been targeted for the reduction of lignin content in the hope of reducing pollution from pulping or improving digestibility of forages. However, transgenic plants with a reduction in COMT activity alone showed a dramatic reduction in syringyl lignin without an apparent decrease in total lignin content (Dwivedi et al, 1994;Atanassova et al, 1995;Doorsselaere et al, 1995;Tsai et al, 1998). This contradicted with the early presumption of COMT as the sole O-methyltransferase (OMT) involved in monolignol biosynthesis.…”
contrasting
confidence: 41%
See 3 more Smart Citations
“…Because COMT was considered to be the sole enzyme involved in methylation, COMT had long been targeted for the reduction of lignin content in the hope of reducing pollution from pulping or improving digestibility of forages. However, transgenic plants with a reduction in COMT activity alone showed a dramatic reduction in syringyl lignin without an apparent decrease in total lignin content (Dwivedi et al, 1994;Atanassova et al, 1995;Doorsselaere et al, 1995;Tsai et al, 1998). This contradicted with the early presumption of COMT as the sole O-methyltransferase (OMT) involved in monolignol biosynthesis.…”
contrasting
confidence: 41%
“…Xylem or wood in plants with repression of COMT or cinnamyl alcohol dehydrogenase often shows strong red coloration, which has been attributed to the accumulation of hydroxycinnamyl aldehydes (Halpin et al, 1994;Higuchi et al, 1994;Ralph et al, 1997;Stewart et al, 1997;Tsai et al, 1998). In plants with repression of 4-coumarate-coenzyme A ligase, xylem displayed a brownish color, probably due to accumulation of hydroxycinnamic acids (Kajita et al, 1997).…”
Section: Coloration Of Wood With Repression Of Ccoaomtmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated impairing different steps in monolignol biosynthesis results in reddish brown to tan stem and stalk pigmentation, including the CAD and COMT mutants examined in this study (Mackay et al 1997, Tsai et al 1998, Sibout et al 2005, Zhang et al 2006). There are differences in pith and midrib (leaf vein) coloration between bmr6 and bmr12 (Porter et al 1978, Saballos et al 2009), probably because bmr6 and bmr12 block different steps of the monolignol biosynthetic pathway.…”
Section: Discussionmentioning
confidence: 99%